An autoethnographic study of realist knowledge translation within sport development. Issue 1 (4th March 2021) - Bailey, Andrew; Harris, Kevin
ABSTRACT: Purpose: This paper provides an autoethnographic account of the knowledge translation process taking place between an academic and a sports development practitioner, regarding mobilising a realist approach to sport development practice. Approach: The paper provides autoethnographic accounts of the knowledge translation process from both academic and practitioner points of view. Utilising the active voice allowed both authors to recreate and reflect on their experiences of the knowledge translation process which took place, applying the model put forward by Clavier et al. (2012 ). Findings: This paper reveals that knowledge translation is neither linear, immediate, or guaranteed to be long-lasting. The findings demonstrate how the power dynamics within the knowledge translation relationship changed over time. Moreover, the reflections demonstrate the impact of mobilising realist practices within sport development. Practical Implications: Highlighting the importance of academics building relationships with key industry stakeholders such as managers and policymakers, the paper reveals that sustainable knowledge translation can only take place if it is done on an organisational level. Research Contribution: Based on the reflections, a model has been produced, demonstrating how knowledge translation manifests itself. The model demonstrates that not one form of knowledge (academic or industry) should be privileged, along with demonstrating the intersection of the two camps.